DENSITY OF MOSQUITOES SPECIES AND EFFECT OF SOME CLIMATIC PARAMETER IN AMINU KANO TEACHING HOSPITAL, KANO, NIGERIA - Haruna, A.; Yayo, A. M.; Mohammed, Y.; Idris, Abdulrazak Muhammad; Takalmawa, H. U.; Aliyu, A. A.; Tsiga-Ahmed, F. I. (FUDMA Journal of Sciences, 2020)
There is a paucity of information on the species of mosquito in Kano City Northern Nigeria. Numerous mosquito control programs that had taken place in Kano State and its environs, mosquitoes remain a problem in the state; therefore a study was undertaken to the relationship between density ofmosquito species and the effect of some climatic parameters on the mosquito distribution in Aminu Kano Teaching Hospital, Kano, Nigeria. The mosquito species were collected using the CDC light trap method and climatic parameters such as temperature and relative humidity were recorded at every one hour of the experiments. A total of 26,652 mosquitoes were collected from January to July 2018. Out of the 26,652, 17444 (65.46%) were Culex speciesand 9208 (34.54%) were Anopheles mosquitoes. Culex species were observed to peak between 10:00 - 11:00 pm (5435) while Anopheles mosquito species were observed to attain their first peak at 3:00 – 4:00 am (3416). High collections of mosquitoes were obtained at 27.10oC and relative humidity of 69.7% and 68.60% for Culicine and Anopheline mosquitoes respectively. This study provided information on the mosquito species diversity in respect to seasonal and periodic variation at AKTH and the effect of some climatic parameters.